Analisis Kurikulum Pendidikan Agama Islam Pada Kurikulum Merdeka - Kulsum, Umi; Ridwan Effendi, Muhamad (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
This analysis examines the implementation of the Independent Curriculum in Islamic Religious Education (PAI) subjects in Indonesia.